STRATEGIC ASPECTS OF ANTI-CRISIS MANAGEMENT OF ENTERPRISES DURING THE COVID-19 PANDEMIC - N. N. Trofimova (Вестник университета)
The article considers the strategic aspects of anti-crisis management of enterprises during the crisis. The paper clarifies the concept of crisis management, analyses the stages of crisis management, and identifies possible threats that arise for enterprises in the current coronavirus pandemic. The use of the the author’s approach, based on the methods of scientific generalization, comparative analysis, system and situational approach, has allowed us to establish that actions taken to manage the crisis should be based on a carefully developed plan, should be effective, and should be applied as soon as possible. The scientific novelty of the study is that, based on the research, the author has identified the advantages of creating a strategic crisis management plan; proposed a sequence of actions for developing an anti-crisis plan; gave an example of implementing an anti-crisis plan for the COVID-19 pandemic; proposed, in order to ensure the sustainability of enterprises in the post-crisis period,  strategic recommendations. The practical significance of this scientific paper is that it can serve as a basis for further research in the field of strategic management based on anti-crisis technologies.